Enhanced Power Conversion Efficiency in Solution‐Processed Rigid CuIn(S, Se)2 and Flexible Cu(In, Ga)Se2 Solar Cells Utilizing Plasmonic Au‐SiO2 Core‐Shell Nanoparticles. Issue 5 (19th March 2019) - Chen, Chia‐Wei; Chen, Yi‐Ju; Thomas, Stuart R.; Yen, Yu‐Ting; Cheng, Lung‐Teng; Wang, Yi‐Chung; Su, Teng‐Yu; Lin, Hao; Hsu, Cheng‐Hung; Ho, Johnny C.; Hsieh, Tung‐Po; Chueh, Yu‐Lun
Abstract : Plasmonic resonance effect triggered by gold nanoparticles (NPs) is utilized to enhance light harvesting in different types of thin‐film solar cells. However, there is no report using the plasmonic resonance effect triggered by metal NPs in chalcopyrite absorber‐based devices because of the high reactivity between the metal NPs and indium/copper/gallium during the required high‐temperature selenization process. In this work, Au NPs encapsulated by a thin protective silicon oxide shell in the chalcopyrite absorber‐based solar cells deposited by scalable solution deposition techniques under the 600 °C selenization process are demonstrated. The increased scattering and surface plasmonic resonance induced field generated by the nanoparticles can lead to significant enhancement in light absorption and charge carrier generation across a broad spectral range. Enhanced power conversion efficiency in solution‐processed rigid CuIn(S, Se)2 from 1.95 to 2.26% and flexible Cu(In, Ga)Se2 solar cells from 9.28% to 10.88% is achieved after the addition of plasmonic Au‐SiO2 core‐shell NPs in the absorber layer. This work demonstrates a facile method for chalcopyrite solar cell enhancement, which is compatible with low‐cost and high‐throughput manufacturing process. Abstract : Enhanced power conversion efficiency in solution‐processed rigid CuIn(S, Se)2 from 1.95 to 2.26% and flexible Cu(In, Ga)Se2 solar cells from 9.28 to 10.88% can be achieved after the addition of plasmonic Au‐SiO2 core‐shell NPs in the absorber layer.